Commentary to the Resolution of the Supreme Court of 24 August 2017 (III CZP 20/17) on the Compensation of Expenses Incurred by the Victim for the Loan of a Substitute Vehicle - Pytkowski, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
In a commentary to the resolution of the Supreme Court regarding the issue of compensation of expenses made on the loan of a substitute means of communication by the victim in a traffic accident, doubts that may arise in the context of case law and practice as well as contradictions in the internal justification of this resolution were indicated. The theoretically correct course of reasoning presented by the Supreme Court presents the arguments derived from the practice and life experience of motor vehicle users, highlighting the idealistic vision of the functioning of the replacement vehicle rental market, presented by the adjudication panel.